Hubungan antara Hardiness dengan Optimisme pada Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) - Renata Sekar Amaris Renata; Ferdinand Hindiarto (Humanitas (Jurnal Psikologi), 2023)
This research was aimed to find correlation between hardiness and optimism on Government Employees with Work Agreement. The hypothesis which is proposed in this research is “a positive correlation between hardiness and optimism on Government Employees with Work Agreement”. There were 122 Government Employees with the Work Agreement in Temanggung district who participated in this research by incidental sampling process. The measurement tools used were optimism scale and hardiness scale were used to find score and relationship between variables which is written in google form. The process to collect data was entirely share the google form link using Whatsapp group. The data analysis technique used is the Pearson product moment correlation. The result showed a correlation coefficient is 0.612 (p > 0,01). Therefore; the hypothesis proposed is accepted, so it is concluded that there a positive relationship between hardiness and optimism in PPPK. The results of this study led to suggestions for the government to provide basic leadership training on hardiness to PPPK before starting the working period. Meanwhile, suggestions for future researchers are to use social support variables to find out whether these variables also contribute to influencing optimism in PPPK.